The Efficacy of Non-Pharmacological Interventions in Reducing Elevated Serum LDL Cholesterol Levels: A Review Paper - Janikowska, Justyna; Wendland, Monika; Zapalska, Barbara Anna; Witkowska, Antonina Teresa; Łubińska-Kowalska, Aleksandra; Domańska, Adrianna; Witkowska, Adrianna; Żak-Gontarz, Agata; Minda, Aleksandra; Długosz, Krzysztof Julian; Piotrowska, Julia (Quality in Sport, 2025)
The review article explores the latest non-pharmacological approaches towards lowering serum levels of a main atherogenic lipoprotein, i.e. low-density lipoprotein (LDL). Elevated low-density lipoprotein cholesterol (LDL-C) levels are associated with a higher risk of cardiovascular disease (CVD)(1). According to World Health Organization (WHO) cardiovascular diseases (CVDs) are the leading cause of mortality worldwide(2). Although drug therapy of elevated LDL-C with statins remains effective, lifestyle modifications should be implemented as a first step in the treatment and also together with prescribed medication for the improved therapeutic outcome. Additionally, the side effects and cost of statins cause more than 30% of patients to discontinue their prescriptions(3), making lifestyle modifications both necessary and increasingly sought after. The article discusses lifestyle changes, particularly dietary adjustments and increased physical activity, and their potential beneficial effects on reducing elevated LDL-C levels. The conclusion emphasizes the critical role of non-pharmacological interventions in managing elevated LDL-C in all patients. Materials and Methods This review article presents a comprehensive and systematic analysis of the current literature on non-pharmacological approaches to managing elevated LDL-C levels. The primary aim was to synthesize and critically assess existing evidence, identify gaps in the research, and propose directions for future investigation. A thorough literature search was conducted across multiple electronic databases, including PubMed, Google Scholar, and Scopus. The search strategy focused on clinical interventions, randomized controlled trials, meta-analyses, and review articles published within the past 20 years.